Neutrophil-lymphocyte ratio as a prognostic tool for the evaluation of laryngeal carcinoma - Sharma, Ashish; Kanaujia, S. K.; Kaushik, Sandeep; Srivastava, Amrita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The objective of the study was to review the neutrophil lymphocyte ratio (NLR) as a prognostic tool in carcinoma larynx. Methods: Patients who were fulfilling inclusion criteria after screening were selected for study. On the basis of cutoff pretreatment NLR (<3 or >3) divided into two groups high pretreatment NLR and low pretreatment NLR. Patient undergo chemo or radiotherapy and at the end of follow up these two group NLR were compared with tumor negative prognostic score, survival at the end of follow up, resolving of symptoms, staging change, tumor regression and overall prognosis at the end of follow up were assessed. Results: Mean value of tumor negative prognostic score of early carcinoma with low NLR, early carcinoma with high NLR, late carcinoma with low NLR and late carcinoma with High NLR were 13.833±2.80, 24.04±4.5538, 37.833±8.68 and 55.33±6.429 respectively. 10 (17.5%) patients with high NLR show more than 50% tumor regression while 17 (29.82%) with high NLR show <50% tumor regression. 26 (45.61%) patients with low NLR show >50% tumor regression and 4 (7.01%) show <50% tumor regression. Conclusions: It was concluded in our study that pretreatment NLR is an acceptable prognostic tool in carcinoma larynx. High NLR was associated with poor prognosis and low NLR was associated with better prognosis.